A Foresight Study of Consumer Readiness on Virtual Fitting Mirror powered by Augmented Reality (AR) in the Fashion Retail Store - An Nisaa Hazeerah Abdul Hakim,; Anim Zalina Azizan, (Research in Management of Technology and Business, 2024)
Virtual fitting mirror is a revolutionary concept that based on the advancements of augmented reality (AR) technology that allows users to digitally explore and experience products in the fashion retail store. This study aims to identify the trends, issues and challenges associated with virtual fitting mirror powered by augmented reality in the fashion retail store and the key drivers on the implementation of virtual fitting mirror and its potential future scenarios. The respondents for this study were visitors at Setia City Mall among Gen Z and Millennial. A questionnaire based on social, technological, environmental, economic, political, and value (STEEPV) drivers will be used to collect respondents’ data. STEEPV analysis, reliability analysis, descriptive analysis and impact-uncertainty analysis used in this study. The data analyzed using the Statistical Package for Social Science (SPSS) software. The ten drivers had been identified and the impact-uncertainty  analysis had been used to identify the future image of consumer readiness on virtual fitting mirror powered by augmented reality in the fashion retail store. A questionnaire was distributed to the visitors at Setia City Mall, Selangor with response rate of 100%. The study found that the drivers of entertainment and engagement and government and policy support have the highest uncertainty and impact and four scenarios were proposed at the end of the study. It were prospering entertainment-drive evolution, policy-led adoption, hybrid innovation eco-fashion and stagnation due to disparity.